Proceedings of the 6th International Symposium on Strength & Conditioning (2017) - Victor Machado Reis; Felipe José Aidar; André Luiz Carneiro; Mário Jorge Costa; Jorge Morais; Henrique Neiva; Rubens Vinicius Letieri; Guilherme Tucher; Nuno Domingos Garrido (Desafio Singular, 2018)
The papers published in these proceedings were submitted to the Scientific Commission of the 6th International Symposium on Strength and Physical Conditioning, held on September 2 and 3, 2017, at the Universitary Centre Estácio of Ceará, Fortaleza, Brazil. Authors are exclusively responsible for the content of the manuscript published. The editors and the Scientific Committee of the 6th International Symposium on Strength and Physical Conditioning assume no responsibility for the opinions and statements expressed by the authors. Partial reproduction of the texts and their use without commercial purposes is allowed, provided that the source/reference is duly mentioned.